Preparation And Characterization Of Carbon Molecular Sieve Membrane From Polyfurfuryl Alcohol - Wan Harun, Wan Mohd Hafiz Faisal (2011)
The application of inorganic membrane would minimize the problems suffered by conventional gas separation technologies such as adsorption, chemical process and polymeric membrane. In this work carbon molecular sieve (CMS) membranes were successfully prepared from polyfurfuryl alcohol (PFA). The CMS membrane substrate was prepared first by coating the dope solution of titania sol onto the titania disk and heated from 300 to 600˚C of sintering temperature. On the other hand, the carbon film was formed by dipping the substrate onto PFA solution followed by carbonization between 400 to 600˚C for 1 to 4 hours of thermal soak times.